Entry Points for Reduction of Greenhouse Gas Emissions in Small-Scale Dairy Farms: Looking Beyond Milk Yield Increase - Vries, Marion de; Zahra, Windi Al; Wouters, Adriaan P.; Middelaar, Corina E.M. van; Oosting, Simon J.; Tiesnamurti, Bess; Vellinga, Theun V. (Frontiers Media, 2019)
Increasing milk yield per cow is considered a promising climate change mitigation strategy for small-scale dairy farms in developing countries. As it can be difficult to increase cow productivity, mitigation options beyond this production strategy need to be identified. The aim of this study was to identify entry points for mitigation of GHG emissions in small-scale dairy farms in Lembang Sub-district, West Java, Indonesia. Data on herd composition, productivity, feeding, and manure management were collected in a survey of 300 randomly selected dairy farms. Characteristics of farms with the 25% lowest (<3291 kg milk/cow/y), medium 50% (3291–4975 kg milk/cow/y), and 25% highest milk yields (≥4976 kg milk/cow/y) were compared. Life cycle assessment was then performed to estimate the cradle-to-farm gate GHG emission intensity (EI) of farms. The relationship between EI and milk yield per cow for all farms was modeled and farms with an EI below and above their predicted EI were compared (“low” and “high” EI farms). Results showed that milk yield explained 57% of the variance in EI among farms. Farms with medium and high milk yields were more often specialized farms, fed more tofu waste and compound feed, and had higher feed costs than farms with low milk yields (P < 0.05). Farms with high milk yields also applied less manure on farm land than farms with low milk yields (P < 0.05). Low EI farms had fewer cows, and fed less rice straw, more cassava waste, and more compound concentrate feed (particularly the type of concentrates consisting largely of by-products from milling industries) than high EI farms (P < 0.05). In addition, low EI farms discharged more manure, stored less solid manure, used less manure for anaerobic digestion followed by daily spreading, and applied less manure N on farmland than high EI farms (P < 0.05). Some associations were affected by confounding factors. Farm management factors associated with milk yield and the residual variation in EI were considered potential entry points for GHG mitigation. Feeding less rice straw and discharging manure, however, were considered unsuitable mitigation strategies because of expected trade-offs with other environmental issues or negative impacts on food-feed competition.